Oral Fluoride Levels 1 h after Use of a Sodium Fluoride Rinse: Effect of Sodium Lauryl Sulfate - Vogel, Gerald L.; Schumacher, Gary E.; Chow, Laurence C.; Tenuta, Livia M.A. (Caries research, 2015)
Increasing the concentration of free fluoride in oral fluids is an important goal in the use of topical fluoride agents. Although sodium lauryl sulfate (SLS) is a common dentifrice ingredient, the influence of this ion on plaque fluid and salivary fluid fluoride has not been examined. The purpose of this study was to investigate the effect of SLS on these parameters and to examine the effect of this ion on total (or whole) plaque fluoride, an important source of plaque fluid fluoride after a sufficient interval following fluoride administration, and on total salivary fluoride, a parameter often used as a surrogate measure of salivary fluid fluoride. Ten subjects accumulated plaque for 48 h before rinsing with a 12 mmol/l NaF (228 µg/g F) rinse containing or not containing 0.5% (w/w) SLS. SLS had no statistically significant effect on total plaque and total saliva fluoride but significantly increased salivary fluid and plaque fluid fluoride (by 147 and 205%, respectively). These results suggest that the nonfluoride components of topical agents can be manipulated to improve the fluoride release characteristics from oral fluoride reservoirs and that statistically significant change may be observed in plaque fluid and salivary fluid fluoride concentrations that may not be observed in total plaque and total saliva fluoride concentrations.